Fishery Crimes: Law Enforcement Challenges in Protecting Marine Resources - Akbar, Sudiono; Hamamah, Fatin (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
Fisheries crimes pose a serious threat to the sustainability of marine resources in Indonesia. Environmental law theory and law enforcement theory are the basis for analyzing the effectiveness of regulations governing the protection of marine ecosystems. The main problem in this study is how the challenges faced in law enforcement against fisheries crimes and the effectiveness of policies that have been implemented. The purpose of this study is to identify obstacles in law enforcement, evaluate existing policies, and provide strategic recommendations to improve the protection of marine resources. This study uses a normative juridical method with a statutory approach and case studies. Data were obtained from positive legal analysis, court decisions, and interviews with law enforcement officers and marine experts. The results of the study show that although regulations such as Law Number 45 of 2009 concerning Fisheries have regulated sanctions for perpetrators of illegal fishing, there are still obstacles in their implementation, including limited patrol facilities, weak coordination between agencies, and corrupt practices.